Confocal surface plasmon microscopy with pupil function engineering - Zhang, Bei; Pechprasarn, Suejit; Zhang, Jing; Somekh, Michael G. (Optical Society of America, 2012)
Surface Plasmon microscopy can measure local changes of refractive index on the micron scale. Interferometric plasmon imaging delivers quantitative high spatial resolution sensitive to refractive index. In addition the so called V(z) method allows image contrast to be controlled by varying the sample defocus without substantially degrading spatial resolution. Here, we show how a confocal system provides a simpler and more stable alternative. This system, however, places greater demands on the dynamic range of the system. We therefore use a spatial light modulator to engineer the microscope pupil function to suppress light that does not contribute to the signal.